2022
DOI: 10.7759/cureus.23920
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Gallbladder in Adult Patients With Type 2 Diabetes Mellitus

Abstract: Introduction and aim: Diabetes mellitus (DM) is one of the most common non-communicable diseases worldwide. Diabetics with autonomic neuropathy tend to have larger gallbladder (GB) with poor contraction after fatty meals predisposing them to gallstones and cholecystitis. This may be prevented and treated if detected early using ultrasound. This study sonographically evaluated the GB in adults with type 2 diabetes and compared the findings with a non-diabetic age and sex-matched control group.Methods: In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Hahms et al, found that gallbladder volume in diabetic patients was signi cantly greater compared with that of controls (19). Also, Ikhuoriah et al found that a signi cant proportion of type 2 diabetics had higher gallbladder volume, gallbladder wall thickness, and presence of gallstone compared to the non-diabetic controls (20). Similarly, Portincasa et al working in Italy were able to establish that patients with gallstone exhibit gallbladder motor dysfunction which manifested as increased fasting and postprandial residual gallbladder volume (21).…”
Section: Discussionmentioning
confidence: 99%
“…Hahms et al, found that gallbladder volume in diabetic patients was signi cantly greater compared with that of controls (19). Also, Ikhuoriah et al found that a signi cant proportion of type 2 diabetics had higher gallbladder volume, gallbladder wall thickness, and presence of gallstone compared to the non-diabetic controls (20). Similarly, Portincasa et al working in Italy were able to establish that patients with gallstone exhibit gallbladder motor dysfunction which manifested as increased fasting and postprandial residual gallbladder volume (21).…”
Section: Discussionmentioning
confidence: 99%